(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate governance is set of principles or guidelines on which a company is governed. It ensures that the corporate works in a way it supposed to work to achieve the desired goals. It makes the corporations accountable to each stakeholder including, directors, shareholders, employees, customers etc. The term governance itself explains the meaning that it is an act of managing a corporate entity. The entity of a corporation is separate from its officials which makes corporate governance an important subject to study. Corporate governance plays an important role to protect the rights of thousands of shareholders, who have ownership in the company but do not play an active role in governing day to day business activities.